Corrected Correlation for Turbulent Convective Heat Transfer in Concentric Annular Pipes - Jinping Xu; Zhiyun Wang; Mo Yang (Energies)
This paper addresses the errors that arise when calculating the convective heat transfer in concentric annular pipes by using the equivalent diameter and turbulent heat transfer formula for circular pipes. This approach employs numerical simulations to solve the Reynolds-averaged Navier–Stokes equations and uses the realizable k–ε turbulence model and a low Reynolds number model near a wall. This study conducts numerical simulations of turbulent convective heat transfer within a concentric annular pipe. The results show that the shear stress on the inner wall surface of the concentric annular pipe and the heat transfer Nusselt number are significantly higher than those on the outer wall surface. At the same Reynolds number, both the entrance length and the peak velocity increase upon increasing the inner-to-outer diameter ratio. A correction factor for the inner-to-outer diameter ratio is proposed to achieve differentiated and accurate predictions for the inner and outer wall surfaces. The results clearly demonstrate the effect of the inner-to-outer diameter ratio on heat transfer.